Analisis Pajak Bumi dan Bangunan Dalam Persepsi Masyarakat di Kecamatan Tilamuta Kabupaten Boalemo - Balada RAF (Universitas Islam Darul Ulum Lamongan, 2019)
Land and buiding tax is the main source ini regional development. This study raised hoh people’s interest in ttheir obligation to the state. As for objectives to be achieved in this studi is to desceribbe the public perception of the obligation to pay taxes in subdistrict of Tilamuta and to find out what factors influence the formation of community persception. This type of research is quantitative descriptive survey research that is taking sampels from a population and using a questionnaire. Aims to explain condition, summarize the various conditions and situation and variables that arise in the community. Based on what happened thes raised to the surface of the character or description of condition of situation and its variables. The population of this research is community of Tilamuta sub-district whose sampels were taken from all villages using the frank linch formula with total of 100 sampel. The results of research data processing show that most respondents know about land and building taxes. The awareness of the community in paying Tilamuta land and building taxes is quite high, this cann be seen from the level of public education that began to improve. The socialization given by the regional government was also quite good but not yet maximized.